Interfacial stress transfer in monolayer and few-layer MoS2 nanosheets in model nanocomposites. (1st March 2023) - Dong, Ming; Young, Robert J.; Dunstan, David J.; Papageorgiou, Dimitrios G.
Abstract: Understanding the stress transfer mechanisms from a polymer matrix to two-dimensional (2D) reinforcements is essential for the preparation of high performance nanocomposites. In this study, the interfacial stress transfer from a flexible polymer substrate to monolayer and few-layer molybdenum disulfide (MoS2 ) under tension has been investigated. Layer-dependent and strain-dependent photoluminescence (PL) spectroscopy were used to examine the stress transfer efficiency. The interlayer stress transfer efficiency of MoS2 was determined to be in the range of 0.76–0.86, higher than that of graphene. The transfer of strain from the polymer substrate to the flakes was derived through strain-dependent band shifts. With progressive loading, the strain distribution in monolayer MoS2 can be described by the shear-lag, partial-debonding and total-debonding models. The interfacial shear and frictional stresses were calculated to quantify the strength of the MoS2 /polymer interface. It was found that the strength of the interface is similar to the strength of a graphene-polymer interface. Strain mapping was performed at different strain levels and it was found that the strain distribution in bilayer MoS2 is similar to the case of a monolayer sample. The interfacial shear strength remains almost unaffected, while the stress transfer length increases with increasing layer number. Graphical abstract: Image 1